Mode B ultrasonography and abdominal Doppler in crab-eating-foxes (Cerdocyon thous) - Silva, Alanna S. L. [UNESP]; Feliciano, Marcus A. R. [UNESP]; Motheo, Tathiana F. [UNESP]; Oliveira, Juliana P. [UNESP]; Kawanami, Aline E. [UNESP]; Werther, Karin [UNESP]; Palha, Maria D. C.; Vicente, Wilter R. R. [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2014)
Annually hundreds of crab-eating foxes (Cerdocyon thous) are referred to rehabilitation centers and zoos in Brazil. The ultrasonographic study of wildlife species is an important tool for a non-invasive and accurate anatomical description and provides important information for wildlife veterinary care. The aim of the present study was to determine the characteristics of the main abdominal organs as well as the vascular indexes of the abdominal aorta and renal arteries of crab-eating foxes (Cerdocyon thous) using mode B ultrasonography and Doppler ultrasonography, respectively. Ultrasonographic features of the main abdominal organs were described and slight differences were noticed between ultrasound imaging of abdominal organs of crab-eating foxes and other species. The bladder presented wall thickness of 12 +/- 0.01 mm, with three defined layers. Both, the right and left kidneys presented corticomedullary ratio of 1: 1 and similarly to the adrenals and the liver, they were homogeneous and hypoechoic compared to the spleen. The spleen was homogeneous and hyperechoic compared to the kidneys. The stomach presented 3 to 5 peristaltic movements per minute, wall thickness of 39 +/- 0.05 mm and lumen and mucosa with hyperechoic and hypoechoic features, respectively. Small and large intestines presented 2 to 3 peristaltic movements per minute, wall thickness of 34 +/- 0.03 mm and three defined layers with hyperechogenic (submucosa and serosa) and hypoechogenic (muscular) features. Ovaries of the female crab-eating fox were hypoechoic compared to the spleen and with heterogeneous parenchyma due to the presence of 2x2 mm ovarian follicles. Prostates of the six males were regular and with a well defined boundary, with a homogeneous and hyperechoic parenchyma compared to the spleen. Vascular indexes of the abdominal aorta (PSV: 25.60 +/- 0.32 cm/s; EDV: 6.96 +/- 1.68cm/s; PI: 1.15 +/- 0.07 e RI: 0.73 +/- 0.07) and right (PSV: 23.08 +/- 3.34cm/s; EDV: 9.33 +/- 2.36cm/s; PI: 1.01 +/- 0.65 e RI: 0.65 +/- 0.16) and left renal arteries (PSV: 23.74 +/- 3.94cm/s; EDV: 9.07 +/- 3.02cm/s; PI: 1.04 +/- 0.31 e RI: 0.64 +/- 0.10) were determined. Thus, conventional and Doppler ultrasonographic imaging provides basic information that can be used as reference for the species as well for other wild canids and it is a precise and non-invasive method that can be safely used to evaluate and diagnose abdominal injuries in these patients.

O objetivo desse estudo foi descrever os achados ultrassonográficos convencionais dos principais órgãos abdominais e determinar com a utilização da ultrassonografia Doppler os índices vasculares da aorta abdominal e artérias renais em cachorros-do-mato (Cerdocyon thous). Foram avaliados nove cachorros-do-mato (Cerdocyon thous). Por meio da ultrassonografia convencional do abdômen dos animais, estudaram-se os achados ultrassonográficos normais e a biometria dos principais órgãos dessa cavidade como fígado, baço, bexiga, estômago, intestinos, adrenais, rins, ovários, próstata e tecido linfoide dos animais, obtendo-se resultados importantes para a caracterização sonográfica desses tecidos. A bexiga apresentou espessura da parede de 12 ± 0,01 mm, com três camadas bem definidas. O rim direito e esquerdo apresentaram relação corticomedular de 1:1 e com ecogenicidade semelhante as adrenais e fígado, homogêneas e hipoecoica em comparação ao baço. O baço apresentou-se homogêneo e hiperecoica em relação aos rins. O estômago apresentou de 3 a 5 movimentos peristálticos por minuto, espessura da parede de 39 ± 0,05mm e lúmen e mucosa com características hiperecoicas e hipoecoicas, respectivamente. O intestino delgado e grosso apresentaram de 2 a 3 movimentos peristálticos por minuto, espessura da parede de 34 ± 0,03mm e três camadas definidas, hiperecogênica (submucosa e serosa) e hipoecogênicas (musculares). Os ovários de uma fêmea se apresentaram hipoecoica, em comparação com o baço, e heterogêneos, devido à presença de folículos ovarianos de 2x2mm de diâmetro. As prostatas de seis machos eram regulares e com contornos definidos, parênquima homogêneo e hiperecoico em relação ao baço. Ao exame Doppler foram determinados os índices vasculares da aorta abdominal (PSV: 25,60±0,32cm/s; EDV: 6,96±1,68cm/s; PI: 1,15±0,07 e RI: 0,73±0,07) e das artérias renais direitas (PSV: 23,08±3,34cm/s; EDV: 9,33±2,36cm/s; PI: 1,01±0,65 e RI: 0,65±0,16) e esquerdas (PSV: 23,74±3,94cm/s; EDV: 9,07±3,02cm/s; PI: 1,04±0,31 e RI: 0,64±0,10). Pode-se concluir que a ultrassonografia convencional e Doppler podem ser ferramentas importantes no estudo morfofisiológico de órgãos abdominais em cachorros-do-mato, possibilitando o diagnóstico de alterações abdominais nesses animais e a utilização desses achados como referências para outros caninos silvestres.
Ultrassonografia abdominal modo B e Doppler em cachorros-do-mato (Cerdocyon thous)
Keywords: Wild mammals; Cerdocyon thous; Abdominal ultrasonography; Doppler